ENT300 (Fundamentals of entrepreneurship) Hawa secret bakery / Nur Farrah Nadia Misman... [et.al] - Misman, Nur Farrah Nadia; Azami, Nur Aziemah; Mohd Yunus, Nur Syafiqah; Jakaria, Amelda; Jasni, Nur Nadhirah Atika (2015)
Hawa Secret Bakery is one of the bakery that serves various types of cakes and buns at Summer Mall, Kota Samarahan, Kuching, Malaysia. While there are many bakery shops everywhere, Hawa Secret Bakery will excel due to its attention detail regarding our users. Through unheralded user’s attention, Hawa Secret Bakery will slowly but surely gain market share as it buns, breads and any other pastry. Moreover, we are believed that we will successfully compete with our competitors in a few years ahead. This is because nowadays parents taking a good care for their children as our bakery also provide vegetarian pastries. We, Hawa Secret Bakery, saw the opportunity that this business has the potential of success provided that it is handled efficiently. The people have always needed food in their life.